Lexical categories verbs, nouns, and adjectives - Baker, Mark C. (Cambridge studies in linguistics, 2003)
For decades, generative linguistics has said little about the differences between verbs, nouns, and adjectives. This book seeks to fill this theoretical gap by presenting simple and substantive syntactic definitions of these three lexical categories. Mark C. Baker claims that the various superficial differences found in particular languages have a single underlying source which can be used to give better characterizations of these 'parts of speech'. These definitions are supported by data from languages from every continent, including English, Italian, Japanese, Edo, Mohawk, Chichewa, Quechua, Choctaw, Nahuatl, Mapuche, and several Austronesian and Australian languages. Baker argues for a formal, syntax-oriented, and universal approach to the parts of speech, as opposed to the functionalist, semantic, and relativist approaches that have dominated the few previous works on this subject. This book will be welcomed by researchers and students of linguistics and by related cognitive scientists of language